Quality of Life in End Stage Breast Cancer Woman and Readmission - Edianto, Edianto; Afriani, Dina (Fakultas Kedokteran, 2024)
Cancer is a health problem that is an important factor in global burden disease. Breast cancer is the most common cancer in women over the world and continues to increase. Quality of life for breast cancer patients becomes very important as the stage of cancer experienced by the patient increases. End stage breast cancer patients tend to experience readmission conditions after they return home from hospitalization. The aim of this study was to determine the quality of life in end stage breast cancer patients with the incidence of readmission. This study used a cross sectional method involving 110 stage 3 and 4 breast cancer patients who were undergoing treatment at the Adam Malik Hospital in Medan, who were sampled consecutively. The research was conducted from July to December 2023. The results of the chi-square analysis showed that the quality of life factors in end stage breast cancer patients that influenced the incidence of readmissions were physical problems with p<0.003 (CI 95%), social problems with p<0.007 (CI 95%), spiritual problems with p<0.030 (CI 95%) and medication problems with p<0.014 (CI 95%). Nursing interventions related to physical, social, spiritual conditions and treatment programs need to be carried out to improve the quality of life in end-stage breast cancer patients so that readmissions can be prevented or reduced